Teatro amador e popular em Osasco: Núcleo Expressão, do sonho a realidade (1971-1979) - Queijo, Elizabeth Aparecida (2020)
The 1970s were marked by the existence of several popular, amateur and semi-professional theatrical groups that sought to get closer to an audience of students and workers from commerce and industry. These groups tried to follow a more popular route and, therefore, closer to this audience to which they performed plays with a more social and sometimes even political questioning about the moment when the country was. Censorship was part of the daily life of these groups and they had to deal with it, seeking the possible gaps for their existence, while resisting the precariousness of the resources that limited them and stimulated their action. This work followed and tries to explain, through the reminiscences of its members and some city periodicals (Jornal Municípios em Marcha and Jornal A Região), the history of the theater group Núcleo Expressão, which was created and developed in the city of Osasco, between from 1971 to 1979, between the so-called “lead years” and the transition to democracy